The Role Of Women In Improving The Family Economy - Zunaidi, Arif; Maghfiroh, Facrial Lailatul (Universitas Trunojoyo Madura, 2021)
The purpose of this study was to determine the role of women in improving the family economy, especially women who work as shallot retail workers. This study uses a qualitative descriptive method, namely formulating a data obtained from words or sentences separated according to the intended category to obtain conclusions. The results of this study conclude that women have a role in helping the family economy. The main reasons why women have to work outside rather than domestic work are economic reasons and self-actualization to help their husbands. The economic demands of the family caused these women to choose to become laborers. Helping husband's finances, to pay needs, and pay arisan.